INTERVIEW WITH JOCHEN WEBER - Magri da Rocha, Guilherme; Galvão Ribeiro Ferreira, Eliane Aparecida (Miscelânea: Revista de Literatura e Vida Social, 2023)
The International Youth Library (Internationale Jugendbibliothek in German) is the world's largest library for international children’s and juvenile/YA literature. Located at Blutenburg Castle in Munich, it is also a renowned scientific research institute that hosts scholars from around the world. With a collection that holds almost 630,000 titles in more than 200 languages, the library’s most important publication is the annual “White Ravens”, a catalog that reunites suggestions of books from different countries. Traditionally, it is published prior to the Frankfurt Book Fair and the books are put on display and introduced at the Bologna Children's Book Fair, the leading professional fair for children's books in the world. Below is an interview with Jochen Weber, responsible for the catalog's editorial work and Head of the library's Language Sections. Mr. Weber graduated with a magister artium degree from the University of Cologne (Germany) where he studied German literature and language, Spanish literature and language, and political science. From 2006 to 2012, he served as vice president of the Arbeitskreis für Jugendliteratur (German section of IBBY).